Empathy moments - Nathalie Barbosa De La Cadena (Trans/Form/Ação)
In this paper, I analyse the act of consciousness called empathy, as proposed by Husserl in Ideas II. By applying Husserl’s phenomenological reduction, I evidence three moments that constitute empathy: first, to recognize the other Ego; second, to open myself up to the other Ego; and third, to feel with the other Ego. I investigate these eidetic universalities [Wesenallgemeinheiten] within the limits of pure intuition (HUA III, 146). To recognize the other Ego is an involuntary act that happens in consciousness when I come face-to-face with another human being. To open myself up to the other Ego is a spiritual act derived from freedom. I can decide whether or not to open myself up. If I do not, empathy is interrupted, incomplete, and I can react either affectionately or distressfully, or I can make a hasty judgement and decide either to distance myself from the other or to act. If I open myself up to the other Ego, I can react affectionately or distressfully, without much information. Another possibility is to comprehend, reflect, judge, agree or disagree, and decide either to distance myself from the other or to act in either a compassionate or a confrontational way. In this regard, empathy does not imply agreeing or acting compassionately. In short, I present a mental map of this reasoning and conclude by pointing out the need to develop empathy and the importance of having time to empathise appropriately.